Absence of Cospeciation between the Uncultured Frankia Microsymbionts and the Disjunct Actinorhizal Coriaria Species - Nouioui, Imen (Hindawi Publishing Corporation, 2014)
Coriaria is an actinorhizal plant that forms root nodules in symbiosis with nitrogen-fixing actinobacteria of the genus Frankia. This symbiotic association has drawn interest because of the disjunct geographical distribution of Coriaria in four separate areas of the world and in the context of evolutionary relationships between host plants and their uncultured microsymbionts. The evolution of Frankia-Coriaria symbioses was examined from a phylogenetic viewpoint using multiple genetic markers in both bacteria and host-plant partners. Total DNA extracted from root nodules collected from five species: C. myrtifolia, C. arborea, C. nepalensis, C. japonica, and C. microphylla, growing in the Mediterranean area (Morocco and France), New Zealand, Pakistan, Japan, and Mexico, respectively, was used to amplify glnA gene (glutamine synthetase), dnaA gene (chromosome replication initiator), and the nif DK IGS (intergenic spacer between nifD and nifK genes) in Frankia and the matK gene (chloroplast-encoded maturase K) and the intergenic transcribed spacers (18S rRNA-ITS1-5.8S rRNA-ITS2-28S rRNA) in Coriaria species. Phylogenetic reconstruction indicated that the radiations of Frankia strains and Coriaria species are not congruent. The lack of cospeciation between the two symbiotic partners may be explained by host shift at high taxonomic rank together with wind dispersal and/or survival in nonhost rhizosphere.